Mindy Kim and the trip to Korea - Lee, Lyla (Lee, Lyla. Mindy Kim, 2021)
Mindy Kim is about to go on her first big trip to Korea! And she cannot wait to: hug her grandparents and eat her Halmoni's homemade cooking! Hang out with her cousins, and see the big sites in Seoul with Dad and his girlfriend, Julie!